2017
DOI: 10.1111/jfpp.13327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrocolloids, sugar, and citric acid on strawberry volatiles in a gummy candy

Abstract: Hydrocolloids and additives in gummy candies can bind strawberry flavor volatiles. The type of hydrocolloid (gelatin, pectin, and starch) and the concentration of the pectin, sugar, and acid, were varied. Volatile concentrations in the headspace of the solutions containing no hydrocolloids were significantly higher than the gels that contained hydrocolloids. Gelatin produced the lowest volatile concentrations compared to pectin or starch, which were not different from each other.Increasing pectin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…As can be seen, within the nongelatin cluster, the products that contained pectin (P1, P5, P6, and P7) were significantly lower in hardness and toughness than those that did not contain pectin. Zhang and Barringer (2018) found that at the same gelling agent concentration (5%) and moisture content (16%), the hardness of pectin and starch jellies, as measured by a compression test, was not statistically different. Their finding does not coincide with our results.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, within the nongelatin cluster, the products that contained pectin (P1, P5, P6, and P7) were significantly lower in hardness and toughness than those that did not contain pectin. Zhang and Barringer (2018) found that at the same gelling agent concentration (5%) and moisture content (16%), the hardness of pectin and starch jellies, as measured by a compression test, was not statistically different. Their finding does not coincide with our results.…”
Section: Resultsmentioning
confidence: 99%
“…Citric acid is used as an antioxidant, a preservative and a taste coregent in hard candies at a concentration of 0–1% [ 54 ] and in gummy candies from 2.5% to 4.5% [ 55 ]. In this study, 0.96% citric acid concentration was not only used as a preservative for the chewable gel tablets but also to produce a better taste.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Most studies have shown that release from starch gels is greater than gelatine gels ( Boland, Buhr, Giannouli, & van Ruth, 2004 ; Kälviäinen, Roininen, & Tuorila, 2000 ; Piccone et al, 2011 ; Zhang & Barringer, 2018 ). Despite this, release was greater of some compounds from the gelatine phase, showing greater affinity for the gelatine phase in a mixed phase matrix, and also that understanding release from a single hydrocolloid matrix may not be directly applicable to a mixed hydrocolloid matrix.…”
Section: Resultsmentioning
confidence: 99%